2021
DOI: 10.3390/insects12020182
|View full text |Cite
|
Sign up to set email alerts
|

(Quasi)-Binomial vs. Gaussian Models to Evaluate Thiamethoxam, Pirimiphos-Methyl, Alpha-Cypermethrin and Deltamethrin on Different Types of Storage Bag Materials Against Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) and Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae)

Abstract: The Mediterranean flour moth, Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) and the confused flour beetle, Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae) are worldwide spread and notorious organisms of numerous stored-products. Both species are dangerous for bagged commodities as penetrators and invaders. The aim of the current study was to examine the efficacy of thiamethoxam, pirimiphos-methyl, alpha-cypermethrin, and deltamethrin, against E. kuehniella and T. confusum larvae, on diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Neurotoxic organochlorines [ 288 , 290 ], organophosphates [ 106 ], pyrethrins, or pyrethroids have been most frequently suggested as active ingredients for the treatment of bags and other packaging [ 287 , 300 ]. Recently, Papanikolaou et al [ 302 ] suggested the application of thiamethoxam, pirimiphos-methyl, alpha-cypermethrin, and deltamethrin to the surface of storage bag materials (plastic and paper) as an efficient management tool against larvae of Ephestia kuehniella Zeller (Pyralidae) and T. confusum . There is, however, concern about the migration of neurotoxic insecticides or other chemicals from treated (primary/secondary) packages into commodities or food.…”
Section: Delivery Of Insecticides As Liquids (Admixtures Liquid Baits Aerosols Sprays Etc)mentioning
confidence: 99%
“…Neurotoxic organochlorines [ 288 , 290 ], organophosphates [ 106 ], pyrethrins, or pyrethroids have been most frequently suggested as active ingredients for the treatment of bags and other packaging [ 287 , 300 ]. Recently, Papanikolaou et al [ 302 ] suggested the application of thiamethoxam, pirimiphos-methyl, alpha-cypermethrin, and deltamethrin to the surface of storage bag materials (plastic and paper) as an efficient management tool against larvae of Ephestia kuehniella Zeller (Pyralidae) and T. confusum . There is, however, concern about the migration of neurotoxic insecticides or other chemicals from treated (primary/secondary) packages into commodities or food.…”
Section: Delivery Of Insecticides As Liquids (Admixtures Liquid Baits Aerosols Sprays Etc)mentioning
confidence: 99%
“…The tested dose of the insecticidal formulation falls within the ranges of both a.i. that have been previously tested for surfaces [46,47]. A separate series of boxes were sprayed only with water to serve as control using a different airbrush.…”
Section: Surface Treatment Bioassaysmentioning
confidence: 99%
“…The strain of the Mediterranean flour moth, Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) was reared on wheat flour at 25 °C and 65% R.H. in continuous darkness (Papanikolaou et al 2021). Larvae of 3rd-4th instar were used in the experiments.…”
Section: Isolation Of α-Amylase (Ec 3211) Activities From Insect Pestsmentioning
confidence: 99%